Acceptance Test and Nutritional Analysis of Aloe Vera Gel a Combination of Rome Beauty Apples as a Potential Treatment to Reduce Cancer Risk - Zahidah Maimunah, Halimah Husniyah Rafifah; Rahmawati, Lusi Anindia; Umami, Zakia (EXSACT-A, 2024)
Aloe vera and Rome Beauty apples have antioxidants, one of which is quercetin, to reduce the risk of cancer and inflammation, but they are less popular as functional foods because their flavors are less desirable. This study aims to determine the acceptability and analyze the nutritional content of aloe vera jelly combined with Rome Beauty apples. This study used an experimental design. The panelists used in this study were 30 people who were semi-trained panelists. The results of the hedonic test on color parameters showed there was a significant difference (p<0.05). The results of the Exponential Comparison Method (MPE) showed that A3 agar was the selected formula. The results of the nutritional content of the selected formula (A3) per 80 gram were energy 64 kcal, protein 1.66 g, fat 0.85 g, carbohydrate 12.32 g, water content 64.89 g, and ash content 0.27 g. The results of the quantitative test showed that the IC50 value of selected formula (A3) was 43,440 ppm and quercetin level 1498.4 mg/80g. It can be concluded that the selected formula has the potential to be a healthy snack to reduce cancer if it is supported by the consumption of other foods that are high in antioxidants.Keywords – Agar, Apple, Aloe Vera, Quercetin